African swine fever virus encodes two genes which share significant homology with the two largest subunits of DNA-dependent RNA polymerases. - Yáñez, R J (1993)
A random sequencing strategy applied to two large SalI restriction fragments (SB and SD) of the African swine fever virus (ASFV) genome revealed that they might encode proteins similar to the two largest RNA polymerase subunits of eukaryotes, poxviruses and Escherichia coli. After further mapping by dot-blot hybridization, two large open reading frames (ORFs) were completely sequenced. The first ORF (NP1450L) encodes a protein of 1450 amino acids with extensive similarity to the largest subunit of RNA polymerases. The second one (EP1242L) codes for a protein of 1242 amino acids similar to the second largest RNA polymerase subunit. Proteins NP1450L and EP1242L are more similar to the corresponding subunits of eukaryotic RNA polymerase II than to those of vaccinia virus, the prototype poxvirus, which shares many functional characteristics with ASFV. ORFs NP1450L and EP1242L are mainly expressed late in ASFV infection, after the onset of DNA replication.